2022
DOI: 10.3390/cells11071163
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Caspase Activity Mediates HMGB1 Release and Differentiation in Myoblasts Affected by Peripheral Arterial Disease

Abstract: Introduction: We previously showed that caspase-1 and -11, which are activated by inflammasomes, mediate recovery from muscle ischemia in mice. We hypothesized that similar to murine models, inflammatory caspases modulate myogenicity and inflammation in ischemic muscle disease. Methods: Caspase activity was measured in ischemic and perfused human myoblasts in response to the NLRP3 and AIM2 inflammasome agonists (nigericin and poly(dA:dT), respectively) with and without specific caspase-1 or pan-caspase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This suggests that the decrease in expression may be due to the loss or atrophy of myo bres and relative over-representation in the cellular mass in the muscle of non-myo bre cell types 68 . Fibrosis is a key feature of muscle pathology in CLTI, and myogenic progenitor cell dysfunction is also observed 12,69,70 . The clinical implications of this remain to be fully understood; however, recent in vivo studies using knockout models, have indicated that Pax7 + myogenic progenitor cells are necessary for regeneration after HLI injury.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the decrease in expression may be due to the loss or atrophy of myo bres and relative over-representation in the cellular mass in the muscle of non-myo bre cell types 68 . Fibrosis is a key feature of muscle pathology in CLTI, and myogenic progenitor cell dysfunction is also observed 12,69,70 . The clinical implications of this remain to be fully understood; however, recent in vivo studies using knockout models, have indicated that Pax7 + myogenic progenitor cells are necessary for regeneration after HLI injury.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CLI severely damages not only blood vessels but also skeletal muscles, which is another critical component of the limb due to poor nutrient supply, and thus it negatively contributes to amputation and eventual limb loss 6,7 . Nevertheless, current therapeutic regimens for treating PAD have focused only on therapeutic angiogenesis by the induction of blood re ow in ischemic limbs through the delivery of growth factors/proteins, genes, or various types of stem cells to ischemic tissues 8,9 . Despite extensive efforts to induce therapeutic angiogenesis, to date the satisfactory rescue of CLI patients from major limb amputation has not been achieved, which may suggest that vascular regeneration alone is insu cient to achieve complete limb salvage 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, CLI severely damages not only blood vessels but also skeletal muscles, which is another critical component of the limb due to poor nutrient supply, and thus, it negatively contributes to amputation and eventual limb loss 6 , 7 . Nevertheless, current therapeutic regimens for treating PAD are focused only on therapeutic angiogenesis by the induction of blood reflow in ischemic limbs through the delivery of growth factors/proteins, genes, or various types of stem cells to ischemic tissues 8 , 9 . Despite extensive efforts to induce therapeutic angiogenesis, to date, satisfactory rescue of CLI patients from major limb amputation has not been achieved, suggesting that vascular regeneration alone is insufficient to achieve complete limb salvage 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%